A STUDY ON THE GENDER EQUALITY AND STATE -WISE FEMALE LITERACY RATE AMONG THE REGIONS IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
Gender inequality is a problem felt by Indian society. Any step towards attaining gender equality must be in the line of inculcating and developing women entrepreneurship and thereby ensuring women empowerment. Women are a vital part of the nation’s economy, constituting one third of the national labour force and a major contributor to the survival of the family. Many governments have made important strides in improving the status of girl’s education. Successful government programmes in Bangladesh, Brazil, Colombia, Kenya, and Mexico, for example, helped more girls gain access to education through scholarships and stipends that help poor families send their daughter to school. Guinea, Guatemala, Peru, Morocco likewise have successfully increased girls school enrolment rates. Despite these gains, however, much more needs to be done to remove gender barriers to learning and literacy for girls. The education gap for girls in developing countries and post-conflict societies remains collective global task. There is a need to continue to work together to lay the foundation for a more sustainable, secure world. The paper attempts to examine the trends of literacy rate, to analyse the gender gap in literacy rate and review the variation in literacy among the regions. The process of economic development in any country is dependent on the availability of human and natural resources. Particularly well educated, trained, qualitative human resources are essential or moreover, it is the key factor in the process of economic development. Education and educational facilities are critical for improving the quality of human resources. Education is the gradual process acquiring knowledge by learning and instruction. Education is a preparation for life which is a result of a good upbringing especially knowledge of correct social behaviour.